+0  
 
+1
65
3
avatar+14 

;-; how do you do this lmao. I tried to brute force it and so everything for the past 3 hours but i cant seem to figure it out

 Sep 15, 2020
 #1
avatar
+1

Since f(x) is divisible by x^3, f(x) is of the form ax^5 + bx^4 + cx^3.

 

You then want ax^5 + bx^4 + cx^3 + 2 to be divisible by (x + 1)^3.  Using long division, you get the equations

-10a  + 6b - 3c = 0

4a - 3b + 2c = 0

-a + b - c + 2 = 0

==> a = 6, b = 16, c = 12

 

So f(x) = 6x^5 + 16x^4 + 12x^3.

 Sep 15, 2020
 #2
avatar+14 
0

that doesnt seem to be right, i also got a similar answer so im not sure whats going on

raphae1  Sep 15, 2020
 #3
avatar+31093 
+3

I get the following:

 Sep 15, 2020

61 Online Users

avatar
avatar
avatar